Quercetin and Idebenone Ameliorate Oxidative Stress, Inflammation, DNA damage, and Apoptosis Induced by Titanium Dioxide Nanoparticles in Rat Liver - Laila M. Fadda; Hanan Hagar; Azza M. Mohamed; Hanaa M. Ali (SAGE Publishing, 2018)
Titanium dioxide nanoparticles (TiO 2 -NPs) are extensively used in a wide range of applications; however, many reports have investigated their nanotoxicological effect at the molecular level either in vitro or in vivo systems. The defensive roles of quercetin (Qur) or idebenone (Id) against the hepatotoxicity induced by TiO 2 -NPs were evaluated in the current study. The results showed that the coadministration of Qur or Id to rats intoxicated with TiO 2 -NPs markedly ameliorated the elevation in hepatic malondialdehyde (MDA), serum alanine amino-transferase (ALT), glucose, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), immunoglobin G (IgG), and C-reactive protein (CRP) levels compared to their levels in TiO 2 -NPs-treated rats. The aforementioned antioxidants also effectively modulated the changes in the levels of serum vascular endothelial growth factor (VEGF), nitric oxide (NO), hepatic DNA breakage, caspase-3, and inhibition of drug metabolizing enzymes (cytochrome P450s; CYP4502E12E1) in rat livers induced by TiO 2 -NPs toxicity. The histopathological examination of the liver section showed that TiO 2 -NPs caused severe degeneration of most hepatocytes with an increase in collagen in the portal region, while treatment with the antioxidants in question improved liver architecture. These outcomes supported the use of Qur and Id as protective agents against the hepatotoxicity induced by TiO 2 -NPs and other hepatotoxic drugs.